Pendampingan Pembelajaran Teknologi Informasi dan Komunikasi Kepada Siswa Madrasah Aliyah Nurul - Syaiful Syaiful; Nur Halizah; Nur Fauziah (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Madrasah Aliyah Nurul Jadid faces challenges in developing limited Information and Communication Technology (ICT) learning. The main problems faced are inadequate ICT infrastructure, lack of teacher ICT knowledge and skills, and lack of structured ICT curriculum. To overcome these problems, community service was carried out using the Community Partnership Program (PKM) method. This PKM includes ICT teacher training, improving ICT infrastructure, and preparing an integrated ICT curriculum. The implemented solutions successfully increased the use of ICT in Madrasah Aliyah Nurul Jadid, improved teacher competence in teaching ICT, and provided a strong foundation for further development in ICT learning. In conclusion, community service with the PKM approach is effective in increasing ICT capacity and infrastructure in madrasahs, supporting the improvement of the quality of education in the digital era.ICT infrastructure